Distance learning during the COVID-19 pandemic for children with ADHD and/or ASD: a European multi-center study examining the role of executive function deficits and age - Lisa B. Thorell; Anselm B. M. Fuermaier; Hanna Christiansen; Ricarda Steinmayr; Dieter Baeyens; Almudena Giménez de la Peña; Madeleine J. Groom; Iman Idrees; Saskia van der Oord; Barbara J. van den Hoofdakker; Marjolein Luman; Irene C. Mammarella; et al. (Child and Adolescent Psychiatry and Mental Health, 2022)
Abstract Background One of the COVID-19 pandemic consequences that has affected families the most is school lockdowns. Some studies have shown that distance learning has been especially challenging for families with a child with neurodevelopmental disorders such as ADHD or ASD. However, previous studies have not taken the heterogeneity of these disorders into account. The aim of the present study was therefore to investigate differences between families with a child with ADHD, ASD, or both conditions, and to examine the role of underlying deficits in executive functioning (EF) in both children and parents in relation to negative and positive effects of distance learning. Methods Survey data assessing both negative and positive experiences of distance learning were collected from parents with a child aged 5–19 years in seven Western European countries: the UK, Germany, Spain, Sweden, the Netherlands, Italy, and Belgium. Altogether, the study included 1010 families with a child with ADHD and/or ASD and an equally large comparison group of families with a child without mental health problems. We included measures of three different types of negative effects (i.e., effects on the child, effects on the parent, and lack of support from school) and positive effects on the family. Results Results confirmed that families with a child with ADHD, ASD or a combination of ADHD and ASD showed higher levels of both negative and positive effects of distance learning than the comparison group. However, few differences were found between the clinical groups. Group differences were more pronounced for older compared to younger children. Regarding the role of both ADHD/ASD diagnosis and EF deficits, primarily children’s EF deficits contributed to high levels of negative effects. Parent EF deficits did not contribute significantly beyond the influence of child EF deficits. Families of children with ADHD/ASD without EF deficits experienced the highest levels of positive effects. Conclusions School closings during COVID-19 have a major impact on children with EF problems, including children with neurodevelopmental disorders. The present study emphasizes that schools should not focus primarily on whether a student has a neurodevelopmental disorder, but rather provide support based on the student’s individual profile of underlying neuropsychological deficits.